Issues in human rights: the plight of Muslim minorities and the lessons therein for Muslim majorities - Babu Sahib, Hikmatullah; Yaacob, Asiah (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2014)
The plight of non-Muslims or other minority communities within a Muslim majority country has been much debated under the broad topic of human rights. Yet problems relating to Muslim minorities in non-Muslim polities have yet to be adequately addressed. More should be done to educate the large Muslim world on the plight of these minority Muslim communities. The lack of focus on the fate of such minorities had resulted in their being subjected to unfair treatment or oppression, painful misery, and unfriendly policies of containment or integration. The authors export other more subtle forms of subjugation more serious than overt oppression and violence. Muslims in adverse minority settings have always struggled to maintain a proper balance between sustaining their religious identity and obligations and maintaining loyalty towards their country. We examine several issues in the light of established human rights principles and identify practical challenges faced in translating these ideals into reality.